Return-to-Office Mandates, Health and Well-Being: Evidence from a Natural Experiment - Chiara Costi; Andrew E. Clark; Conchita D'Ambrosio; Anthony Lepinteur; Giorgia Menta (Institute of Labor Economics (IZA), 2024)
We here exploit an exogenous shift in working conditions for public-sector workers in Italy to establish the causal effect of a return-to-office (RTO) mandate on worker health and well-being. In nine waves of quarterly panel data we first find a significant fall in teleworking for those affected by the RTO mandate, who also spend more time outdoors, work fewer hours, and interact less with relatives and friends. The net effect of these lifestyle changes on a battery of health and well-being measures following the return to office work is insignificant. The place of work post-pandemic has neither positive nor negative health implications.
Keywords: I18; I31; J88; 330; return to office; working from home; health; well-being